Analysis of Students' Critical Thinking Skills in Solving SDGs-Based Contextual Mathematics Problems - Dede Irman; Vera Vera (International Journal of Ethno-Sciences and Education Research, 2026)
This study, entitled "Analysis of Students' Critical Thinking Skills in Solving SDGs-Based Contextual Mathematics Problems," aims to analyze junior high school students' critical thinking skills in solving contextual mathematics problems designed based on the Sustainable Development Goals (SDGs) theme. The study was conducted using a qualitative descriptive approach through open-ended written tests and in-depth interviews with six students with high, medium, and low academic ability categories. Data were analyzed based on four critical thinking indicators: interpretation, analysis, inference, and evaluation. The results showed significant variations among student ability categories. High-ability students were able to understand the context, connect quantitative data with reality, draw logical conclusions, and critically evaluate alternative solutions, especially on the theme of clean water scarcity (SDG 6). In contrast, students with medium and low abilities still faced difficulties in transferring narrative information to mathematical models and justifying evidence-based answers. These findings indicate that the integration of SDGs-based problems in mathematics learning effectively promotes higher-order thinking skills, global awareness, and students' reflective attitudes towards sustainability issues. However, the success of this approach requires strengthening quantitative literacy, ongoing contextual guidance, and the development of challenging yet relevant test instruments. Practically, this research emphasizes the importance of synergy between a contextual learning approach and the principles of the Independent Curriculum to develop a generation of critical, socially aware learners who are ready to face global challenges.